Stalk rots are associated with the early maturity of hybrid corn - Berghetti, Juliano; Ferreira, Evandro Zacca; Casa, Ricardo Trezzi; Scheidt, Bruno Tabarelli; Martins, Flavio Chupel; Gonçalves, Mayra Juline (Revista de Ciências Agroveterinárias, 2020)
Stalk rots of corn are responsible for significant decreases in grain yield. The aim of this study was to examine the relationship between the incidence of stalk rots and the maturity cycle of six corn hybrids. The experiment was conducted in the field, where 70,000 seeds ha-1 of the commercial hybrids P32R22 YHR and AG9045 VT PRO (super early) and P30F53 Hx, DKB250 VT PRO2, AS1656 VT PRO2, and AG8025 VT PRO (early) were sown in October in the 2012/2013 and 2013/2014 crop years. A randomized block design with four replications was applied, and five linear meters were evaluated in each plot. The incidence of stalk rot was determined by the presence of discoloration and lower stalk resistance. Ears from healthy and infected plants were separately screened to determine the percentage loss. Losses caused by stalk rot due to the severity of the disease may vary depending on the hybrid, even if their maturity cycles have similar characteristics. The fungi detected in the stalks were Stenocarpella sp., Colletotrichum graminicola, Fusarium graminearum, and F. verticillioides. All of the hybrids in the study exhibited symptoms of stalk rot as they showed no resistance, but different degrees of susceptibility were observed among the tested materials. The hybrid AG8025 VT PRO demonstrated the least susceptibility to stalk rots. The super early hybrids P32R22 YHR and AG9045 VT PRO had a higher incidence than early-maturity hybrids, thus indicating that faster maturity is associated with a greater susceptibility to stalk rots.